Водні джерела та фонтани Криму в контексті ісламських традицій - Акчуріна-Муфтієва, Н. (Інститут мистецтвознавства, фольклористики та етнології ім. М.Т. Рильського НАН України, 2007)
The article is devoted to construction of water resources and fountains in Crimea. The author gives the typology review on the purpose and compositional decision of fountain constructions and classifies them into four basic groups: «cheshme» - sources of water, springs; «Abdest fountains» - for ritual washing before preying; small fountain yards and pavilions; «Sabil» - sacred, paradisal springs. The author underlines the fact that art of fountain construction in Crimea had a sacred basis being kept on fundamental layers of Islam philosophy, conception of work of art synthesis with surrounding nature, usage of symbolism, allowing «to read» the content of a building as a Koran page.